Collaboration with an infection control team promoted appropriate antibiotic use for third molar extraction at a Japanese hospital. Issue 6 (June 2020) - Yoshida, Hisato; Matsuda, Shinpei; Aratani, Tomonori; Tsukamoto, Hitoshi; Yoshimura, Hitoshi; Sano, Kazuo; Iwasaki, Hiromichi
Abstract: Oral antibiotic therapy is routinely administered when a third molar (M3) is extracted to prevent infectious complications after surgery. Oral third-generation cephalosporins are frequently used after M3 extraction in Japan but at the expense of an increased risk of antimicrobial resistance. Therefore, the infection control team (ICT) at our institution recommended a reduction in use of these agents after M3 extraction. In this study, we compared the types of antibiotic agents prescribed for patients undergoing M3 extraction before and after this recommendation. We investigated the relationship between type of antibiotic used and the likelihood of infectious complications as well as cost savings in patients who underwent M3 extraction in the 6 months before and after the ICT recommendation in July 2018. There was a marked reduction in use of oral third-generation cephalosporins after M3 extraction ( P < 0.0001) and increased use of oral penicillins and first-generation cephalosporins after the ICT recommendation. Moreover, surgical site infection (SSIs) were significantly less common after the ICT recommendation ( P = 0.0099); however, the SSI rate was higher in patients who received a third-generation cephalosporin than in those who received penicillin (8.8% vs 0.5%). There was also a significant saving in per-patient antibiotic costs after the ICT recommendation (269.5 ± 282.0 JPY vs 454.7 ± 376.6 JPY; P < 0.0001). These findings suggest that collaboration with an ICT promotes appropriate antibiotic use, decreases the risk of an SSI, and improves the cost-benefit ratio in patients undergoing M3 extraction.